Knowledge, attitude and practice of insulin use and its adverse effects in adult diabetic population - T., Nivethitha; S., Manickavasagam; M., Paramasivam; G., Sai Thaejasvi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes is a disease when left untreated, leads to many complications. India is emerging as a diabetic capital of the world. Insulin is widely used as a therapeutic option, and hence this study was conducted to assess the awareness of Insulin use and its adverse effects in diabetic population. Methods: The study was a questionnaire survey conducted in adult patients with diabetes who are on Insulin therapy. The participants’ knowledge, attitude and practice were assessed by using a questionnaire consisting of 32 questions. Scores were allotted to each question, and evaluated after applying appropriate statistical tests. Results: The mean age of the participants was 57.26±11.24 years. About 54% were males. 46% belonged to rural areas. The mean knowledge score was 17.53±4.40, mean attitude score 7.42±4.85 and the mean practice score was 6.56±1.91. 40% responded that they will return the expired insulin vials to the pharmacy. The most common reason for non adherence was economical constraints (60%). The females had better knowledge (17.60±4.43 vs. 17.45±4.40, p>0.88), attitude (8.21±3.84 vs. 6.58±5.56, p>0.09) and practice (6.97±1.84 vs. 6.13±1.92, p<0.02) of insulin use than males. Also, the urban population had better knowledge (17.58±3.64 vs. 17.32±4.97, p>0.297), attitude (8.70±3.95 vs. 6.06±5.37, p <0.002) and practice scores (6.92±1.89 vs. 6.38±1.92, p>1.395) than the rural counterparts. Conclusions: There exists a gap between knowledge attitude and practice of insulin use. This can be overcome by conducting awareness programmes by health care providers, to sensitise people about the proper use, side effects and the methods of disposal of insulin vials.